An Integrated Investigation into the Socioeconomic Factors Threatening Crop Marketing: A Comparative Study on Faryab Province of Afghanistan and the Sistan Region of Iran - Mawladad Khairi; Mahdi Safdari; Ali Sardar Shahraki (Environmental Energy and Economic Research)
The income and livelihood of most rural families in Iran and Afghanistan depend on the agricultural sector so that this sector is the biggest source of employment in these countries. However, crop marketing is in very poor condition in these countries. The research is an applied study in goal and uses a mixed-method (qualitative and quantitative). The data collection instrument was a questionnaire filled by experts in Faryab province Afghanistan and experts in the Sistan region, Iran. So, a total of 40 Afghani and Iranian experts were asked to fill out the questionnaire. The Afghan experts included academic teachers and the senior employees of agriculture, irrigation, and finance and the Iranian experts included academic teachers and the employees of the Agriculture Jahad Organization. The fuzzy SAW technique was used in MCDMsolver 2018 for modeling. The results are presented with reasoning from the perspectives of the Iranian and Afghan experts. The results as to the opinions of 20 Iranian experts and 20 Afghan experts about 8 criteria and 40 sub-criteria were divided into different steps and were analyzed with tables and graphs. From the viewpoint of the Iranian experts, the sub-criteria of ‘insufficient infrastructure facilities’ with a weight of 2.574, ‘abuse of brokers and intermediaries in reducing crop prices’ with a weight of 2.508, ‘lack of supporting financial institutions’ with a weight of 2.444, ‘lack of capital and credit’ with a weight of 2.409